2011
DOI: 10.1111/j.1447-0756.2011.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D receptor BsmI genotype on the response to osteoporosis treatment in postmenopausal women: A pilot study

Abstract: These preliminary results indicate that alendronate has a differential effect on BMD, depending on the VDR genotype. Carriers of the b allele may be more responsive to treatment compared to patients with the BB genotype. The interaction of VDR's BsmI polymorphism with the efficacy of the anti-osteoporotic treatment needs further investigation by larger prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
11
0
6
Order By: Relevance
“…The prevalence of the BB genotype in the studied population was 16.4 %, which is similar to the prevalence observed in other samples of Caucasians populations [32, 33], proving that our sample was representative. Since we investigated women with a specific disease—that is with a specific phenotype—the results seem to be no less valuable than the results of population studies.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of the BB genotype in the studied population was 16.4 %, which is similar to the prevalence observed in other samples of Caucasians populations [32, 33], proving that our sample was representative. Since we investigated women with a specific disease—that is with a specific phenotype—the results seem to be no less valuable than the results of population studies.…”
Section: Discussionsupporting
confidence: 88%
“…No known functional consequence of this variant has been described; however, a few studies have found that it is associated with antiresorptive treatment responses [40,41,47,48]. In a study on the effectiveness of antiresorptive treatment in postmenopausal women, treatment outcomes (i.e.…”
Section: Important Variantsmentioning
confidence: 99%
“…Так, в исследовании M. Creatsa и соавт. [15] показана связь полиморфизма BsmI гена VDR с эффективностью лечения ОП азотсодержащим бисфосфонатом алендро-натом у женщин в постменопаузе. Носители аллели b полиморфизма BsmI гена VDR характеризовались поло-жительным ответом на лечение алендронатом, а нега-тивный ответ был выявлен у носителей генотипа ВВ.…”
Section: Discussionunclassified
“…Носители аллели b полиморфизма BsmI гена VDR характеризовались поло-жительным ответом на лечение алендронатом, а нега-тивный ответ был выявлен у носителей генотипа ВВ. При лечении терипаратидом такая ассоциация обнару-жена не была [15]. В статье S. Palomba и соавт.…”
Section: Discussionunclassified
See 1 more Smart Citation